(untitled) (Jurnal Bahasa, 2005)
The Malay and Chinese society inherited collections of proverb but Malay proverb was more known by the plural society in Malaysia. By examining carefully 30 Malay proverbs and 30 Chinese proverbs, the researcher seek to find similarity in meaning between the two. Besides that, the researcher applied theory of deconstruction as to examine the existence of entity, binary oppositions, and dominant hierarchy in Malay and Chinese proverb. The finding revealed compatibility and parallelism rather than dissimilarity in meanings derived from think-ing and life experience perpetuated by the Malays and Chinese via proverb. Selection of element in the creation of each other proverb did indicate a difference while discussing the same phenomenon.